The cartographic representation of vertical home in Baghdad government - عذراء عبد حمد حسام صاحب ال طعمة (College of Education for Women, 2019)
The cartographic representation of geographical phenomenon considers the essential base in geographical analysis since as it supports the vertical house which is apartment houses consist of apartments which represent civil phenomenon , the aim of this study is to project the rule of cartographic representation methods in geographical analysis and make comparison in economic and social aspects for two approaches , the vertical and construction building methods. The expand of city horizontally represent a problem in itself because it leads to loss of civil lands and overpass the agricultural lands as a result ,the ratio of habitation of land usage is so large in comparison with another usages of lands of the cities ; therefore ; many countries went to use the method of vertical building with a numerous families , their height range between (4-3 ) stairs ,this house buildings describes with suitable higher population densities , efficient and economic usage of lands and minimize the costs of housings to confront the large sufficiency in population requirements , the costs of apartments considers more lesser than the costs of the individual houses ;therefore ; it serves the ability of limited revenue categories especially if it use alternative building materials like light concrete which is cheaper than tradition material like stairs for example plus to social positive sides for that kind of housing that associated with social interaction among living families in vertical construction.